Children's Commodification on Baim Paula's YouTube Channel - Aqila Tazkia Nafsa; Abraham Zakky Zulhazmi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
The commodification of children's phenomena on social media raises various problems. This research aims to reveal the children's commodification on Baim Paula's YouTube channel. Through this research, the authors hope to provide advantages to raise awareness of YouTubers or influencers to be more aware of creating content that involves children. This research uses a qualitative descriptive method with a discourse analysis approach of Norman Fairclough. The object of the research is conducted by analyzing the children's commodification of Lala. The data collection technique used is documentation of two videos on Baim Paula's channel related to the children's commodification. The analysis of Baim Paula's contents shows that commodification tends to be the commodification of content. It manifested in the child's commodification of Lala. Even though positively, Lala gets a place to develop her talent. The massive development of social media makes commodification carried out by any media user easily. It could be that the perpetrators are unaware that they have carried out a form of child's commodification into a commercially valuable. Hence, it benefits media users, in this case, Baim Paula.